Homoserine lactones influence the reaction of plants to Rhizobia - Zarkani, Azhar A.; Stein, Elke; Röhrich, Christian R.; Schikora, Marek; Evguenieva-Hackenberg, Elena; Degenkolb, Thomas; Vilcinskas, Andreas; Klug, Gabriele; Kogel, Karl-Heinz; Schikora, Adam; Justus Liebig University Giessen (My University, 2013)
Bacterial quorum sensing molecules not only grant the communication withinbacterial communities, but also influence eukaryotic hosts. N-acyl-homoserine lactones(AHLs) produced by pathogenic or beneficial bacteria were shown to induce diversereactions in animals and plants. In plants, the reaction to AHLs depends on the length ofthe lipid side chain. Here we investigated the impact of two bacteria onArabidopsis thaliana, which usually enter a close symbiosis with plants from the Fabaceae(legumes) family and produce a long-chain AHL (Sinorhizobium meliloti) or a short-chainAHL (Rhizobium etli). We demonstrate that, similarly to the reaction to pure AHLmolecules, the impact, which the inoculation with rhizosphere bacteria has on plants,depends on the type of the produced AHL. The inoculation with oxo-C14-HSL-producingS. meliloti strains enhanced plant resistance towards pathogenic bacteria, whereas theinoculation with an AttM lactonase-expressing S. meliloti strain did not. Inoculation withthe oxo-C8-HSL-producing R. etli had no impact on the resistance, which is in agreementwith our previous hypothesis. In addition, plants seem to influence the availability of AHLsin the rhizosphere. Taken together, this report provides new insights in the role ofN-acyl-homoserine lactones in the inter-kingdom communication at the root surface.
Keywords: quorum sensing; induced resistance; plant-bacteria interaction; homoserine lactones; ddc:630